Prevalence and Resistance Patterns of Candida albicans in Diabetic and Non-Diabetic Patients with Urinary Tract Infections - Prijana, Christian; Parwati, Ida; Prihatni, Delita (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: Candida spp. is an opportunistic fungi genus that can turn into pathogens, especially in those with inadequate immune response such as in patients with diabetes mellitus (DM), of which Candida albicans is the most common species. This study aimed to determine the prevalence and antifungal resistance patterns of Candida albicans in DM and non-DM patients with urinary tract infections (UTIs).Methods: A retrospective descriptive observational study was conducted in 2023 using medical record data of DM and non-DM patients with UTIs who were treated at a tertiary hospital in Bandung, Indonesia from July 2019 to December 2021. Data on patient characteristics, proportion of fungal species causing UTI, and antifungal resistance patterns of Candida albicans were analyzed using Microsoft Excel 2019 and presented in tabular form and chart.Results: Of a total 291 patient data, 21 were DM patients and 270 were non-DM patients, mostly were female, 71.4% and 58.2%, respectively. The prevalence of Candida albicans in DM patients was 66.7% and in non-DM patients was 70.7%, mostly resistant to micafungin (7.1% and 8.9%, respectively).Conclusion: Female is more susceptible to UTIs. More than half of DM and non-DM patients with UTIs are infected with Candida albicans, and mostly resistant to micafungin. Antifungal treatment guidelines based on resistance patterns and education on personal hygiene to prevent UTIs are recommended.